Experience with the use of Acrobat in the CAJUN publishing project - Brailsford, David F. (Association for Computing Machinery (ACM), 1994)
Adobe's Acrobat software, released in June 1993, is based around a new Portable Document Format (PDF) which offers the possibility of being able to view and exchange electronic documents, independent of the originating software, across a wide variety of supported hardware platforms (PC, Macintosh, Sun UNIX etc.). The fact that Acrobat's imageable objects are rendered with full use of Level 2 PostScript means that the most demanding requirements can be met in terms of high-quality typography and device-independent colour. These qualities will be very desirable components in future multimedia and hypermedia systems. The current capabilities of Acrobat and PDF are described; in particular the presence of hypertext links, bookmarks, and yellow sticker annotations (in release 1.0) together with article threads and multi-media plugins in version 2.0, This article also describes the CAJUN project (CD-ROM Acrobat Journals Using Networks) which has been investigating the automated placement of PDF hypertextual features from various front-end text processing systems. CAJUN has also been experimenting with the dissemination of PDF over e-mail, via World Wide Web and on CDROM.